ANALISIS PENENTUAN JARAK TITIK INFORMASI DAN KLASIFIKASI SUMBER DAYA ENDAPAN NIKEL LATERIT BERDASARKAN ANALISIS VARIOGRAM - Irfan Marwanza; Chairul Nas; Theresa Naomi Putri; Ahmad Helman Hamdani; Iyan Haryanto (PPSDM Geominerba, 2017)
Estimation process of precipitated mineral deposit is usually done by using conventional method which is only based on sample position. The accurate estimation method, that includes spatial and temporal continuity, is considered important, and a method that takes account of this continuity is Kriging Method. A study will be conducted by making laterite nickel zonation, based on degree of drill core (coring), while content appraisal and nickel resource comparison in block model will use Kriging Method. Data of this study is taken from southern block exploration of PT. Haltim, Wailukum, district of East Halmahera, North Maluku. Description method isused to analyse assay data, lithology, collar, and bore hole survey. Analysis method is done by using Surpac 6.3 software. Through block model result, it is found that the spread of nickel, ferrum, MgO, SiO2 and cobalt is in every percentage of the level. This method will generate experimental Variogram using lag value, nugget effect and sill that should be taken into account to make an accurate estimation result. The classification is done based on thickness and weighting of saprolite zone in southern block. The result of classification using sill method for saprolite zone is one third sill for measuring area of 35 meter, and two third sill for appointed area of 55 meter. For that reason, in this study area, for 50 meter gap of bore hole is classified as appointed area.